Synthesis, Characterization and Determination of Weight Poly Molecule (Lactic acid) - Saefuddin Saefuddin; Peter Davey (Jurnal Penelitian Pendidikan IPA, 2023)
Experiments have been successfully carried out to react with lactic acid and 1,4-butanediol, tin (II) chloride dihydrate (SnCl2.2H2O), chloroform, methanol, liquid nitrogen, nitrogen gas, and silicone oil at various concentrations. The objective exists to synthesize polylactic acid by forming polylactic acid diol (PLA-OH) via a direct polycondensation reaction of lactic acid and 1,4-butanediol in a glass reactor following a specific reaction scheme. Synthesis was carried out using different amounts of reagents according to the predetermined mole ratio of lactic acid (AL) and 1,4-butanediol (BD). The FTIR, 1H NMR, and GPC analyses that characterized the PLA-OH revealed its physicochemical characteristics. The FTIR and 1H NMR characterization results show new absorption peaks and a shift in PLA-OH absorption peaks. It indicates that a bond has been formed from the reaction between lactic acid molecules and 1,4-butanediol to produce PLA-OH. From the spectrum analysis, it can be concluded that the structure of the synthesized PLA-OH has four different proton environments (there are four different peaks in the spectrum). The peaks originate from the protons in methylene (-OCH2CH2CH2CH2O), internal methine (-O-CH-), and methine at the end of the PLA-OH chain, as well as proton peaks in methyl (H3C-). The characterization results with GPC showed that the tendency to increase Mn PLA was directly proportional to the increasing amount of lactic acid in the PLA chain